Výroba čepu pro šnekový dopravník - Drmota, Josef (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Cílem této bakalářské práce je sestavení technologického postupu výroby součásti „čep pro šnekový dopravník“ a jeho následná výroba. V první části je zvolen vhodný materiál a navržen polotovar pro výrobu součásti. Následuje návrh technologického postupu výroby a výroba součásti. Závěrečná část je věnována porovnání a shrnutí dosažených výsledků.

The aim of this bachelor thesis is the compilation of technological procedur of manifacturing of the component called the pin screw conveyor and its subsequent production. In the first part is chosen suitable material and semi-product for the production. Following part deals with proposal of the technological procedure of manufacturing and production of the component. The final part is devoted to the comparison and summary of the results.
Production for the Pin Screw Conveyor
Keywords: čep; šnekový dopravník; obrábění; technologický postup výroby; výroba součásti; pin; screw conveyor; machining; technological procedure of manufacturing; manufacturing of the component